Complete remission in a pretreated, microsatellite-stable, KRAS-mutated colon cancer patient after treatment with sintilimab and bevacizumab and platinum-based chemotherapy: a case report and literature review - He, Lijuan; Li, Haiyuan; Wang, Yunpeng; Li, Weidong; Gao, Lei; Xu, Bo; Hu, Jike; He, Puyi; Pu, Weigao; Sun, Guodong; Wang, Zhuanfang; Han, Qinying; et al. (Frontiers in Immunology, 2024)
Metastatic colon cancer remains an incurable disease, and it is difficult for existing treatments to achieve the desired clinical outcome, especially for colon cancer patients who have received first-line treatment. Although immune checkpoint inhibitors (ICIs) have demonstrated durable clinical efficacy in a variety of solid tumors, their response requires an inflammatory tumor microenvironment. However, microsatellite-stable (MSS) colon cancer, which accounts for the majority of colorectal cancers, is a cold tumor that does not respond well to ICIs. Combination regimens open the door to the utility of ICIs in cold tumors. Although combination therapies have shown their advantage even for MSS colon cancer, it remains unclear whether combination therapies show their advantage in patients with pretreated metastatic colon cancer. We report a patient who has achieved complete remission and good tolerance with sintilimab plus bevacizumab and platinum-based chemotherapy after postoperative recurrence. The patient had KRAS mutation and MSS-type colon cancer, and his PD-1+CD8+ and CD3−CD19−CD14+CD16−HLA-DR were both positive. He has achieved a progression-free survival of 43 months and is still being followed up at our center. The above results suggest that this therapeutic regimen is a promising treatment modality for the management of pretreated, MSS-type and KRAS-mutated metastatic colorectal cancer although its application to the general public still needs to be validated in clinical trials.